PEMANFAATAN REAL TIME CONFERENCE DALAM BIDANG PENGEMBANGAN KOMPETENSI PADA ERA DISRUPTIVE TECHNOLOGY - Setiadiputra, R Yudhy Pradityo (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2019)
Human resources (HR) is an important part in an organization. Both private organizations and public sector organizations in an effort to improve service to their stakeholders can do several things, one of the most optimal organizational efforts is the development of human resource competencies. Competence development can be done in various ways, both classical like face to face meetings or modern like e-learning. Given the rapid development of desruptive technology era, the development of human resources competency, especially ASN in this case, must also take advantage of the growing information technology. E-learning that has been done by many agencies of ASN competence development development at this time, still need many adjustments. This is because the implementation of e-learning is still there are things that need to be adjusted include the assessment of results that are not objective in learning with e-learning method. To minimize it, can use new learning method that is real time conference method. This method is a method like classical face-to-face method, but this method uses good technological media so that it can be done at once in some classes / space competence development.